Palladium-catalyzed oxidative annulation of pyrrolylalkyl-1H-azoles: towards the synthesis of polyheterocyclic arenes - Tripathi, Krishna N.; Bansode, Avinash H.; Singh, Ravi P. (Synthesis-Stuttgart, 2020)
A highly efficient and regioselective palladium-catalyzed annulation protocol for a series of linear and terminally substituted 1,2- and 1,3-di(heteroaryl)alkanes to the corresponding polyheterocyclic arenes is reported. Herein, intramolecular oxidative coupling involving double C(sp(2))-H bond functionalization provides a feasible access to biheteroaryl systems annulated to a six-membered ring. The methodology is not restricted to six-membered annulations and was extended to the synthesis of compounds with a seven-membered ring and biheteroaryl core.
Keywords: C-H functionalization; imidazoles; oxidative coupling; Palladium; pyrroles